Editorial - Forestaction Nepal (Journal of Forest and Livelihood, 2025)
In this issue of the Journal of Forest and Livelihood, we introduce research articles around community forestry that focuses on landscape restoration, ecological resilience, and livelihood improvement and shed light on how they may lead to sustainable resource management.